Preparation method and application of spherical activated carbon
Patent Information
- Application Number
- CN202211605783.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-14
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2042-12-14
AI Technical Summary
Traditional methods for preparing spherical activated carbon suffer from problems such as high wear, small particle size, easy aggregation, poor structure, high dust content, and wide particle size distribution, making it difficult to achieve the industrial production of high-performance adsorbents.
A gelatinous slurry was formed by mixing activated carbon precursor powder with gellan gum, which was then dropped into the oil phase to form gel spheres. After drying and heat treatment, monodisperse spherical activated carbon with controllable particle size was prepared by utilizing the low-temperature coagulation characteristics of gellan gum.
The preparation process is simple, and the product has low ash content, good sphericity, and high mechanical strength, making it suitable for large particle fluidized beds. As an excellent adsorbent, it has broad application prospects.
Smart Images

Figure HDA0003998882290000011
Abstract
Description
Technical Field
[0001] This application relates to a method for preparing spherical activated carbon and its application, belonging to the field of materials preparation technology. Background Technology
[0002] Spherical activated carbon exhibits low fluid resistance when used in fixed beds, making it an ideal adsorbent and catalytic material widely used in chemical protection, catalyst support, and biomedicine. Traditional methods for preparing spherical materials mainly include suspension polymerization, roll forming, and spray granulation. Suspension polymerization requires a dispersant, which is difficult to remove from the polymer product after polymerization, affecting polymer performance. Roll forming is limited to producing carriers with larger diameters, resulting in less than ideal product strength, generating significant dust, high product wear, and large particle size deviations. Spray granulation suffers from smaller particle size, poor structure, undesirable surface properties, and low mechanical strength.
[0003] Patent 2020112310714 discloses a method for preparing phenolic resin microspheres. The method involves mixing phenol, formaldehyde, a curing agent, a suspending agent, and a solvent in a specific ratio, adding the mixture to a reaction vessel, stirring, and heating. After washing with water, filtration, and drying, phenolic resin microspheres are obtained. These microspheres are then cured, carbonized, and activated to obtain activated carbon spheres. However, this method produces carbon spheres with a wide particle size distribution, making it difficult to obtain spherical activated carbon with a concentrated particle size range. Summary of the Invention
[0004] The purpose of this application is to provide a novel method for preparing spherical activated carbon, which has a fast forming speed, simple process, and is easy to realize industrial production. It solves the problems of high wear, small particle size, easy aggregation, poor structure, and heavy dust pollution in traditional methods. The resulting product has the advantages of low impurity ash content, large particle size, good sphericity, smooth surface, good adsorption performance, and high mechanical strength, and can be used as a high-performance adsorbent.
[0005] According to one aspect of this application, a method for preparing spherical activated carbon is provided, comprising the following steps:
[0006] (1) Dissolve activated carbon precursor powder and gellan gum in water and stir to obtain a colloidal slurry;
[0007] (2) The gel-like slurry is dropped into the oil phase to form gel spheres;
[0008] (3) After drying the gel balls, they are impregnated in an adhesive and heat-treated to obtain the spherical activated carbon.
[0009] Optionally, the activated carbon precursor powder is selected from at least one of natural solid polymers, synthetic solid polymers, coal, pitch, carbon black, and activated carbon.
[0010] Optionally, the natural solid polymer is at least one of starch, cellulose, lignin, protein, nutshell, and wood.
[0011] Optionally, the synthetic solid polymer is at least one selected from phenolic resin, melamine resin, epoxy resin, furan resin, polyvinyl chloride, polyacrylonitrile, polyurethane, polystyrene, and polyvinyl alcohol.
[0012] Optionally, the activated carbon precursor in the colloidal slurry has a mass percentage of 5-50%, and the gellan gum has a mass percentage of 0.05-6%.
[0013] Optionally, the mass percentage of activated carbon precursor in the colloidal slurry is any value or a range between two values from 5%, 10%, 20%, 30%, 40%, and 50%.
[0014] Optionally, the mass percentage of gellan gum in the gelatinous slurry is any value or a range between two values, which is 0.05%, 0.1%, 1%, 3%, 5%, or 6%.
[0015] Optionally, in step (2), the oil phase is at least one of mineral oil, vegetable oil and organosilicon oil.
[0016] Optionally, the adhesive is selected from at least one of phenolic resin, melamine resin, epoxy resin, polyacrylonitrile, furan resin, polyurethane, coal tar, asphalt, sucrose, fructose, and glucose.
[0017] Optionally, the mass ratio of the adhesive to the activated carbon precursor powder is 1:0.05 to 0.5.
[0018] Optionally, the mass ratio of the adhesive to the activated carbon precursor powder is 1:0.1 to 0.3.
[0019] Optionally, the mass ratio of the adhesive to the activated carbon precursor powder is any value or a range between two values from 1:0.05, 1:0.1, 1:0.2, 1:0.3, 1:0.4, and 1:0.5.
[0020] Optionally, in step (1), the stirring temperature is 60 to 100°C, and the stirring time is 0.1 to 10 hours.
[0021] Optionally, in step (2), the temperature of the oil phase is 0 to 50°C.
[0022] Optionally, the temperature of the oil phase is 10–30°C.
[0023] Optionally, the temperature of the oil phase is any value or a range between two of the following: 0°C, 10°C, 20°C, 30°C, 40°C, and 50°C.
[0024] Optionally, in step (3), the temperature of the heat treatment is 450 to 1200°C, and the time of the heat treatment is 0.1 to 24 hours.
[0025] Optionally, the heat treatment temperature is 600–1000°C, and the heat treatment time is 1–6 hours.
[0026] Optionally, the temperature of the heat treatment is any value or a range between two of the following: 450℃, 550℃, 600℃, 650℃, 750℃, 850℃, 950℃, 1000℃, 1100℃, and 1200℃.
[0027] Optionally, the heat treatment time is any value or a range between two values from 0.1h, 1h, 3h, 6h, 12h, 15h, 20h, and 24h.
[0028] Optionally, the atmosphere for the heat treatment is at least one of N2, Ar, CO2, and water vapor.
[0029] Optionally, the drying temperature is 30–200°C.
[0030] Optionally, the immersion time is 0.1 to 72 hours.
[0031] According to another aspect of this application, spherical activated carbon obtained by the above preparation method is provided, wherein the particle size range of the spherical activated carbon is 0.1 to 10 mm.
[0032] Optionally, the mechanical strength of the spherical activated carbon is 2 to 70 N.
[0033] According to another aspect of this application, the above-mentioned spherical activated carbon is provided for use in adsorbents and catalysts.
[0034] The beneficial effects that this application can produce include:
[0035] This application introduces a method of mixing gellan gum with a polymer precursor to obtain a mixed slurry, which is then dripped into an oil phase and cooled. Utilizing the low-temperature coagulation characteristic of gellan gum, monodisperse spherical activated carbon with controllable particle size is prepared. This preparation process is simple, and the resulting spherical carbon has low impurity ash content, good sphericity, smooth surface, high mechanical strength, good dispersibility, and large particle size, meeting the requirements of large-particle fluidized beds. As a high-performance adsorbent, it has broad application prospects. Attached Figure Description
[0036] Figure 1This is a diagram of spherical activated carbon from Example 1 of this application. Detailed Implementation
[0037] The present application is described in detail below with reference to the embodiments, but the present application is not limited to these embodiments.
[0038] Unless otherwise specified, all raw materials used in the embodiments of this application were purchased through commercial channels.
[0039] Example 1
[0040] 30g of carbon black precursor powder was mixed with water and gellan gum to prepare a gelatinous slurry with an activated carbon precursor content of 35% and a gellan gum content of 1% at 85℃. The slurry was then dropped into phenyl silicone oil in a 10℃ ice-water bath using a pelletizing machine to form gel balls. After cooling and solidification, the balls were washed and dried, then impregnated with epoxy resin in a mass ratio of adhesive to activated carbon precursor powder of 0.1. The mixture was then heat-treated at 750℃ for 5 hours under an Ar atmosphere to obtain monodisperse spherical activated carbon with controllable particle size.
[0041] Example 2
[0042] 30g of carbon black precursor powder was mixed with water and gellan gum to prepare a gelatinous slurry with an activated carbon precursor content of 35% and a gellan gum content of 2% at 60℃. The slurry was then dropped into phenyl silicone oil in a 10℃ ice-water bath using a pelletizing machine to form gel balls. After cooling and solidification, the balls were washed and dried, then impregnated with epoxy resin with an adhesive-to-activated carbon precursor powder mass ratio of 0.15. The mixture was then heat-treated at 900℃ for 4 hours under an Ar atmosphere to obtain monodisperse spherical activated carbon with controllable particle size.
[0043] Example 3
[0044] 30g of furan resin precursor powder was mixed with water and gellan gum to prepare a gelatinous slurry with an activated carbon precursor content of 40% and a gellan gum content of 2% at 90℃. The slurry was then dropped into phenyl silicone oil in a 15℃ ice-water bath using a pelletizing machine to form gel balls. After cooling and solidification, the balls were washed and dried, then impregnated with epoxy resin in a mass ratio of adhesive to activated carbon precursor powder of 0.1. The mixture was then heat-treated at 850℃ for 4 hours under an Ar atmosphere to obtain monodisperse spherical activated carbon with controllable particle size.
[0045] Example 4
[0046] 30g of polyvinyl chloride precursor powder was mixed with water and gellan gum to prepare a gelatinous slurry with an activated carbon precursor content of 40% and a gellan gum content of 1.5% at 95℃. The slurry was then dropped into phenyl silicone oil in a 15℃ ice-water bath using a pelletizing machine to form gel balls. After cooling and solidification, the balls were washed and dried, then impregnated with epoxy resin with an adhesive-to-activated carbon precursor powder mass ratio of 0.2. The mixture was then heat-treated at 850℃ for 6 hours under an Ar atmosphere to obtain monodisperse spherical activated carbon with controllable particle size.
[0047] Example 5
[0048] 30g of polyurethane precursor powder was mixed with water and gellan gum to prepare a gelatinous slurry with an activated carbon precursor content of 45% and a gellan gum content of 1% at 70℃. The slurry was then dropped into phenyl silicone oil in a 5℃ ice-water bath using a pelletizing machine to form gel balls. After cooling and solidification, the balls were washed and dried, then impregnated with epoxy resin with an adhesive-to-activated carbon precursor powder mass ratio of 0.2. The mixture was then heat-treated at 950℃ for 3 hours under an Ar atmosphere to obtain monodisperse spherical activated carbon with controllable particle size.
[0049] Example 6
[0050] 30g of phenolic resin precursor powder was mixed with water and gellan gum to prepare a gelatinous slurry with an activated carbon precursor content of 20% and a gellan gum content of 4% at 70℃. The slurry was then dropped into phenyl silicone oil in a 20℃ ice-water bath using a pelletizing machine to form gel balls. After cooling and solidification, the balls were washed and dried, then impregnated with phenolic resin in a phenolic resin mixture with an adhesive to activated carbon precursor powder mass ratio of 0.4. The mixture was then heat-treated at 800℃ for 5 hours under an Ar atmosphere to obtain monodisperse spherical activated carbon with controllable particle size.
[0051] Example 7
[0052] 40g of furan resin precursor powder was mixed with water and gellan gum to prepare a gelatinous slurry with an activated carbon precursor content of 20% and a gellan gum content of 3.5% at 75℃. The slurry was then dropped into ethyl silicone oil in a 20℃ ice-water bath using a pelletizing machine to form gel balls. After cooling and solidification, the balls were washed and dried, then impregnated with phenolic resin in a 0.45 mass ratio of adhesive to activated carbon precursor powder. The mixture was then heat-treated at 800℃ for 3 hours under a N2 atmosphere to obtain monodisperse spherical activated carbon with controllable particle size.
[0053] Example 8
[0054] 40g of epoxy resin precursor powder was mixed with water and gellan gum to prepare a gelatinous slurry with an activated carbon precursor content of 25% and a gellan gum content of 3% at 65℃. The slurry was then dropped into ethyl silicone oil in a 25℃ ice-water bath using a pelletizing machine to form gel balls. After cooling and solidification, the balls were washed and dried, then impregnated with phenolic resin in a 0.35 mass ratio of adhesive to activated carbon precursor powder. The mixture was then heat-treated at 700℃ for 8 hours under a N2 atmosphere to obtain monodisperse spherical activated carbon with controllable particle size.
[0055] Example 9
[0056] 40g of epoxy resin precursor powder was mixed with water and gellan gum to prepare a gelatinous slurry with an activated carbon precursor content of 25% and a gellan gum content of 3.5% at 65℃. The slurry was then dropped into ethyl silicone oil in a 25℃ ice-water bath using a pelletizing machine to form gel balls. After cooling and solidification, the balls were washed and dried, then impregnated with phenolic resin in a 0.5 mass ratio of adhesive to activated carbon precursor powder. The mixture was then heat-treated at 600℃ for 16 hours under a N2 atmosphere to obtain monodisperse spherical activated carbon with controllable particle size.
[0057] Example 10
[0058] 40g of polyvinyl alcohol precursor powder was mixed with water and gellan gum to prepare a gelatinous slurry with an activated carbon precursor content of 50% and a gellan gum content of 0.5% at 75℃. The slurry was then dropped into ethyl silicone oil in a 30℃ ice-water bath using a pelletizing machine to form gel balls. After cooling and solidification, the balls were washed and dried, then impregnated with phenolic resin in a 0.05 mass ratio of adhesive to activated carbon precursor powder. The mixture was then heat-treated at 650℃ for 14 hours under a N2 atmosphere to obtain monodisperse spherical activated carbon with controllable particle size.
[0059] Example 11
[0060] 35g of polyvinyl alcohol precursor powder was mixed with water and gellan gum to prepare a gelatinous slurry with an activated carbon precursor content of 30% and a gellan gum content of 3.5% at 80℃. The slurry was then dropped into ethyl silicone oil in a 30℃ ice-water bath using a pelletizing machine to form gel balls. After cooling and solidification, the balls were washed and dried, then impregnated with phenolic resin in a 0.45 mass ratio of adhesive to activated carbon precursor powder. The mixture was then heat-treated at 1000℃ for 1 hour under a CO2 atmosphere to obtain monodisperse spherical activated carbon with controllable particle size.
[0061] Example 12
[0062] 45g of starch precursor powder was mixed with water and gellan gum to prepare a gelatinous slurry with an activated carbon precursor content of 10% and a gellan gum content of 5.5% at 80℃. The slurry was then dropped into ethyl silicone oil in a 35℃ ice-water bath using a pelletizing machine to form gel balls. After cooling and solidification, the balls were washed and dried, then impregnated with phenolic resin in a 0.5 mass ratio of adhesive to activated carbon precursor powder. The mixture was then heat-treated at 450℃ for 22 hours under a CO2 atmosphere to obtain monodisperse spherical activated carbon with controllable particle size.
[0063] Example 13
[0064] 35g of activated carbon precursor powder was mixed with water and gellan gum to prepare a gelatinous slurry with an activated carbon precursor content of 5% and a gellan gum content of 6% by mass at 100℃. The slurry was then dropped into ethyl silicone oil in a 5℃ ice-water bath using a pelletizing machine to form gel balls. After cooling and solidification, the balls were washed and dried, then impregnated with phenolic resin in a 0.5 mass ratio of adhesive to activated carbon precursor powder. The mixture was then heat-treated at 1200℃ for 0.5 hours under a CO2 atmosphere to obtain monodisperse spherical activated carbon with controllable particle size.
[0065] Example 14
[0066] 50g of polyvinyl chloride precursor powder was mixed with water and gellan gum to prepare a gelatinous slurry with 5% activated carbon precursor and 6% gellan gum by mass at 90℃. The slurry was then dropped into ethyl silicone oil in a 50℃ ice-water bath using a pelletizing machine to form gel balls. After cooling and solidification, the balls were washed and dried, then impregnated with phenolic resin with an adhesive-to-activated carbon precursor powder mass ratio of 0.45. The mixture was then heat-treated at 550℃ for 17 hours under a CO2 atmosphere to obtain monodisperse spherical activated carbon with controllable particle size.
[0067] Example 15
[0068] 25g of carbon black precursor powder was mixed with water and gellan gum to prepare a gelatinous slurry with a carbon precursor content of 15% and a gellan gum content of 5% at 95℃. The slurry was then dropped into ethyl silicone oil in a 45℃ ice-water bath using a pelletizing machine to form gel balls. After cooling and solidification, the balls were washed and dried, and then impregnated with phenolic resin with an adhesive-to-carbon precursor powder mass ratio of 0.25. The mixture was then heat-treated at 500℃ for 18 hours under a CO2 atmosphere to obtain monodisperse spherical activated carbon with controllable particle size.
[0069] After testing, the particle size range of the spherical activated carbon prepared in Examples 1 to 15 was found to be 0.1–10 mm. Figure 1 It can be seen that the particle size range of spherical activated carbon is 5-7 mm.
[0070] The mechanical strength of the spherical activated carbon prepared in Examples 1 to 15 was measured to be 2 to 70 N using a particle strength tester.
[0071] The above description is merely a few embodiments of this application and is not intended to limit this application in any way. Although this application discloses preferred embodiments as described above, it is not intended to limit this application. Any changes or modifications made by those skilled in the art without departing from the scope of the technical solution of this application using the disclosed technical content are equivalent to equivalent implementation cases and fall within the scope of the technical solution.
Claims
1. A method for preparing spherical activated carbon, characterized in that, Includes the following steps: (1) Dissolve activated carbon precursor powder and gellan gum in water and stir at 60-100℃ for 0.1-10h to obtain a colloidal slurry; the mass percentage of activated carbon precursor in the colloidal slurry is 5-50% and the mass percentage of gellan gum is 0.05-6%; the activated carbon precursor powder is selected from at least one of natural solid polymers, synthetic solid polymers, coal, asphalt, carbon black and activated carbon; (2) The gel-like slurry is dropped into silicone oil at a temperature of 0-50°C to form gel spheres; (3) The gel spheres are dried at 30-200°C and then immersed in an adhesive for 0.1-72 h. Then, they are heat-treated at 450-1200°C for 0.1-24 h under N2, Ar, CO2 or water vapor atmosphere to obtain the spherical activated carbon. The adhesive is selected from at least one of phenolic resin, melamine resin, epoxy resin, polyacrylonitrile, furan resin, polyurethane, coal tar, asphalt, sucrose, fructose and glucose. The mass ratio of the adhesive to the activated carbon precursor powder is 1:0.05~0.
5.
2. The preparation method according to claim 1, characterized in that, The natural solid polymer is at least one of starch, cellulose, lignin, protein, fruit shell and wood; The synthetic solid polymer is at least one of phenolic resin, melamine resin, epoxy resin, furan resin, polyvinyl chloride, polyacrylonitrile, polyurethane, polystyrene, and polyvinyl alcohol.
3. The preparation method according to claim 1, characterized in that, The mass ratio of the adhesive to the activated carbon precursor powder is 1:0.1~0.
3.
4. The preparation method according to claim 1, characterized in that, In step (2), the temperature of the silicone oil is 10~30℃.
5. The preparation method according to claim 1, characterized in that, In step (3), the temperature of the heat treatment is 600~1000℃ and the time of the heat treatment is 1~6h.
6. A spherical activated carbon obtained by the preparation method according to any one of claims 1 to 5, characterized in that, The particle size range of the spherical activated carbon is 0.1~10 mm; The mechanical strength of the spherical activated carbon is 2~70N.
7. The application of the spherical activated carbon according to claim 6 in the fields of adsorbents and catalysts.
Citation Information
Patent Citations
Preparation method of spherical molecular sieve
CN105289755A
Preparation method for resin based carbon micro-sphere adsorbing material
CN106824089A
